1993
DOI: 10.1021/bi00085a009
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen equilibrium properties of asymmetric nickel(II)-iron(II) hybrid hemoglobin

Abstract: Asymmetric Ni(II)-Fe(II) hybrid hemoglobin, XL[alpha(Fe)beta(Fe)][alpha(Ni)beta(Ni)], in which the alpha 1 beta 1 dimer containing ferrous protoporphyrin IX and the complementary alpha 2 beta 2 dimer containing Ni(II) protoporphyrin IX were cross-linked between Lys-82 beta 1 and Lys-82 beta 2 by reaction with bis(3,5-dibromosalicyl) fumarate, was synthesized and characterized. We have previously shown that (i) Ni(II) protoporphyrin IX, which binds neither oxygen nor carbon monoxide, mimics a fixed deoxyheme wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 47 publications
(76 reference statements)
2
23
1
Order By: Relevance
“…Also unlike HbA, no major quaternary changes occur upon binding of oxygen to HbI (the heavy-atom RMSD between the liganded and unliganded structure of HbI is 1.3 Å ), and the tertiary structural changes are small and localized near the heme group. Nevertheless, HbI is highly cooperative; the binding of oxygen to its two equivalent binding sites has a Hill coefficient of 1.5 (Chiancone et al 1981;Ikeda-Saito et al 1983), similar to the value (1.36-1.72) for human hemoglobin (HbA) when two of the Fe +2 are replaced by nonreactive Ni +2 (Shibayama et al 1993). Thus, the mechanism of cooperativity must be very different from that of the vertebrate hemoglobins described above.…”
Section: Cooperativity In Dimeric Hemoglobin: Water-mediated Allostermentioning
confidence: 91%
“…Also unlike HbA, no major quaternary changes occur upon binding of oxygen to HbI (the heavy-atom RMSD between the liganded and unliganded structure of HbI is 1.3 Å ), and the tertiary structural changes are small and localized near the heme group. Nevertheless, HbI is highly cooperative; the binding of oxygen to its two equivalent binding sites has a Hill coefficient of 1.5 (Chiancone et al 1981;Ikeda-Saito et al 1983), similar to the value (1.36-1.72) for human hemoglobin (HbA) when two of the Fe +2 are replaced by nonreactive Ni +2 (Shibayama et al 1993). Thus, the mechanism of cooperativity must be very different from that of the vertebrate hemoglobins described above.…”
Section: Cooperativity In Dimeric Hemoglobin: Water-mediated Allostermentioning
confidence: 91%
“…Since the nickel atoms remain five-coordinated, they stabilize the T-structure. Shibayama et al found the average K 1 s of the nickel-iron hybrids to be close to the first Adair constant of normal human hemoglobin, which suggested that permutations of such hybrids could serve as models of intermediates in the reactions of hemoglobins with ligands (48,49).…”
Section: Incompatibility With Free Energy Of Cooperativitymentioning
confidence: 99%
“…To represent the oxygenation intermediates of Hb A, the hybrids in group (i) and (iii) are particularly important. In our recent series of studies, Ni(II)-Fe(II) hybrid Hbs in group (iii) have been used successfully to investigate the structures and functions of the intermediates appearing in the first half oxygenation of Hb A (21)(22)(23)(24)(25)(26)(27)(28). Although the Ni(II)-Fe(II) hybrid system has brought much structural and functional information about the initial-half oxygenated intermediates, this approach could not be extended to studies on the latter-half oxygenation of Hb A.…”
mentioning
confidence: 99%